Antiarrhythmic activity in occlusion‐reperfusion model of 1‐(1H‐indol‐4‐yloxy)‐3‐[2‐(2‐methoxyphenoxy)ethyl]amino propan‐2‐ol and its enantiomers. (January 2016) - Bednarski, Marek; Otto, Monika; Dudek, Magdalena; Siwek, Agata; Zygmunt, Małgorzata; Knutelska, Joanna; Nowiński, Leszek; Groszek, Grażyna; Sapa, Jacek
Summary: Acute myocardial infarction (AMI) is a leading cause of mortality and morbidity worldwide, especially in developed countries. The most serious problem after myocardial infarction is reperfusion injury that manifests as functional impairment, arrhythmia, and accelerated progression of cell death in certain critically injured myocytes. Subsequently the infarcted myocardium develops features of necrosis and reactive inflammation. To reduce lethal reperfusion injury in patient with AMI antioxidants, anti‐inflammatory agents, adenosine, opioids, metabolic modulators (glucose, insulin, and potassium, nicorandil and agents which reduce intracellular Ca 2+ overload and inhibit Na + ‐H + exchange) are used. In this study a novel compound (compound 9) 1‐(1 h‐indol‐4‐yloxy)‐3‐[2‐(2‐methoxyphenoxy) ethyl]aminopropan‐2‐ol and its enantiomers are examined in arrhythmia associated with coronary artery occlusion and reperfusion in a rat model. Antioxidant properties are also determined for test compounds using the malondialdehyde (MDA) lipid peroxidation and ferric reducing antioxidant power (FRAP) tests. In summary, the tested compounds, especially the S enantiomer has a strong antiarrhythmic activity in a model of occlusion and reperfusion of the left coronary artery which is probably related to their adrenolytic action. In contrast to carvedilol, none of the test compound reduced the lipid peroxidation but increased ferric reducing antioxidant power. In the antioxidant effect, there was no difference between the optical forms of compound 9.